Methodology of the Complex Analysis of Statistical Information Collections (Exemplified by “Kharkiv Calendar”, 1869-1917): Study Experience - Янкул, О.М. (My University, 2022)
The present research deals with the publication “Kharkiv calendar” as one of the specific sources of local history. It should be rightfully attributed as a separate type of periodicals – “statisticalinformation collection”. Similar publications were spread in almost all regions of the Russian Empire in the 19th and early 20th centuries and were named “calendars” or “memorable books”. They have their own specifics and therefore need special approach for their study. According to his own experience, the author presents certain directions of investigation of these sources. It may be suggested the following steps of work with them: identifying of the specificity and transformations of the structure of these sources (separation of traditional and novel rubrics); analysis of balance between local, all-imperial and worldwide data (there was dynamics of this information); classification of scientific and popular-science materials; periodization of functioning of periodicals; focus on specificity of gathering of statistical information that had published in these collections.